Investigation on shock-induced reaction characteristics of an Al/Ni composite processed via accumulative roll-bonding. (15th February 2017) - Ji, Cheng; He, Yuan; Wang, Chuan Ting; He, Yong; Pan, Xuchao; Jiao, Junjie; Guo, Lei
Abstract: An Al/Ni composite was produced via accumulative roll-bonding (ARB) process up to four cycles. The shock-induced reaction behavior of the material was investigated by means of a quasi-sealed test chamber. The results demonstrated that the Al/Ni composite fabricated by ARB underwent chemical reaction when impacted onto steel target. The energy released by reaction led to significant pressure rise inside the quasi-sealed chamber. It was shown that the amount of energy increased with the increasing of impact velocity. A relationship between the pressure inside the chamber and the impact velocity was derived to analyze the effect quantitatively. The results of this study represented the potential of Al/Ni composite processed by ARB as reactive fragments. Graphical abstract: Highlights: A bulk Al/Ni composite was successfully fabricated by accumulative roll-bonding processing. The impact velocity plays important role on controlling reaction efficiency of Al/Ni composite. A theoretical model was built to evaluate the experimental results, which showed relatively good accuracy.